The Covid-19 Pandemic: Impacts on Hotel Workers’ Job Stress, Well-Being and Self-Assessed Mental Health at the Nusa Dua Bali - Prijanka, Mariska; Trisdiarto, Tommy; Abdullah, Edwin Hidayat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The aim of this research was to identify the impacts of Covid-19 pandemic on hotel workers’ job stress, well-being and self-assessed mental health at The Nusa Dua luxury tourism complex in Bali. In order to achieve the aim, a survey was conducted on 400 hotel workers from 21 upscale international and local hotel brands at The Nusa Dua by using measurement items that were already tested in several past studies. The data were analyzed by implementing three statistical techniques which were the exploratory factor analysis, confirmatory factor analysis, and path analysis. This study found that the Covid-19 pandemic distresses had positively impacted job stress and that job stress had negatively impacted the hotel workers’ well-being. This research also revealed that job stress had positively impacted self-assessed mental health. Moreover, the analysis found that economic distresses were the most concerning issue for the hotel workers at The Nusa Dua during the Covid-19 pandemic. This result was different compared to the past study in Korea which found that physical concerns were the main issue. In accordance with the previous research, this study also revealed that the higher the job stress, the more impact it had on the hotel workers’ self-assessed mental health. Overall, it was found that the social perception distresses and job stress had the highest correlation with other variables. Due to the time limitation of this research, there may have been other indicators relevant to the context of Indonesian hospitality workers that were not identified. Hence, this study recommends future research to conduct focus group discussion or in-depth interviews with suitable key informants to identify aspects that may be more relevant.